Новий міжродовий гібрид ×Pyralus kursakovii (Rosaceae) - Mezhenskyj, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The new intergeneric hybrid Pyralus kursakovii nothosp. nov. (Malus prunifolia (Willd.) Borkh. × Pyrus communis L.) is described and illustrated.